Family Disaster Planning Untuk Meningkatkan Pengetahuan dan Sikap Disabilitas Dalam Menghadapi Bencana - Brigitta Ayu Dwi Susanti; Eva Nurlina Aprilia (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: The family as the smallest unit in society has a share in disaster preparedness, especially for families with disabilities, this is due to the lack of disaster management for families with disabilities. According to a 2013 UN global survey, worldwide 20% of people with disabilities can save themselves and 31% of people say they need someone who can help during a disaster. Imogiri Bantul District is the red zone that suffered the worst damage and from the results of preliminary studies disaster prepared families have not been formed in real terms. Aims of this study is to analize effect pamily disaster planning to improve knowledge and ability disability person in disaster. Methods: Quasi eksperiment pre and post test without control. Research instrument with preparedness instrument. There are 31 subjects in this research. Results: Knowledge and attitude to prepare disaster in disabilities can improve significantly p<0.005 (Wilcoxon test). Conclusion: With family disaster planning the knowledge and attitude can improve significantly to prepare disaster in disabilities and their family.